Multimedia-Based Hypercontent Module Development for Early Childhood Education during Covid-19 Pandemic - Hamsar Hasfat (SEAMEO CECCEP, 2022)
Implementation of early childhood education during Covid-19 pandemic is a new challenge for teachers and parents. Therefore, it is necessary to develop a hypercontent module for early childhood education because the module does not only contain material in text form that can be read or viewed by students but also contains learning videos that contain direct explanations from the teachers regarding certain materials and animations that possible to increase students' interest. This hypercontent module for early childhood education research will be developed using ADDIE development model consists of 5 steps, Analysis, Design, Development, Implementation, and Evaluation. The Hypercontent module is developed based on the results of studies and analysis of learning needs, after that product development is carried out in the form of a multimedia-based hypercontent module that will be validated by experts, the module is then tested by teachers and students (parents) to produce a valid Hypercontent Module for PAUD, practical or easy to use by teachers and students as well as parents who accompany students to study from home. The multimedia-based hypercontent module entitled